Searching for a Threshold effect in the Diversification-profitability Relationship. Evidence from the MENA Banks - Khemiri, Mohamed Ali (International Journal of Economics and Financial Issues, 2023)
This paper investigates the non-linear relationship between bank diversification and bank profitability in the MENA region. More specifically it checks whether there exists a threshold effect in the diversification-profitability relationship. To achieve this goal, we used a panel of 83 retail MENA banks during the period 2005-2020 and we performed the Panel Smooth Transition Regression (PSTR) model as empirical approach. The results confirm the existence of a threshold effect in the non-interest income and bank profitability relationship. To get benefit from bank diversification, the ratio of non-interest income in the MENA region should exceed 22% when profitability is ROA and 25.41% for ROE. Below these thresholds, bank diversification significantly decreases the level of bank profitability. The findings of this research have substantial implications for both policymakers and bankers. The MENA banks should be engaged in more diversified bank activities in order to enhance their overall revenues.